Sweatshop - Bagge, Peter 1957- (Fantagraphics Books Inc, 2015)
Mel Bowling is the unhappy, out-of-touch creator of a very bad daily comic strip called Freddy Ferret. He spends most of his time listening to Rush Limbaugh and coming up with horrible catchphrases for his merchandise, while his "sweatshop" team of artists do all the hard work